The linguistic feature differences of gender roles among UiTM students in weblog: a case study / Hoo Fang Jing, Raihan Ibrahim and Mohd Razif Ibrahim - Fang Jing, Hoo; Ibrahim, Raihan; Ibrahim, Mohd Razif (Faculty of Administrative Science and Policy Studies, 2012)
Weblogs is one of the developments in Computer-Mediated Communication (CMC) whereby they are easy to use, free to the public, and can encourage self-expression as well as self-presentation among the users. Due to the features mentioned, this text-based social communication mode has attained widespread popularity among both female and male students in universities. Thus, this study examined the gender roles on patterns of online interaction and organization in weblogs among UiTM students. Twelve students (six male and six female students) from the Faculty of Computer Science UiTM Alor Gajah Melaka, participated in the study. The aim of this study is to investigate how linguistic features in terms of punctuation marks and capital letters, code switching and blogging jargons were used to express ideas, feelings and experiences and thoughts when posting on weblogs. A qualitative research design was adopted in the data collection. Direct-observation was used as the instrumentation in this study and percentile method was applied to measure differences and similarities of gender roles from the data gained in the weblogs created. The comments and posted articles were analysed based on the linguistic features identified in this study. The findings suggest that firstly weblogs contained gender similarities and differences when looking at the linguistic features. This could be seen in the use of punctuation marks and capital letters that show that the male bloggers were more conscious than the female bloggers. Secondly, there were no obvious gender differences in the created weblog in this study. This was especially true in the features like code-switching and jargons. Finally, the similarities shown in this study has proven that weblogs were easy to use by both the male and female bloggers. It can be concluded that the significance of this study is to view the ways the weblog community is expected to interact (norms) based on gender roles in weblogs.